Enhancing Nateglinide Delivery Through Mucoadhesive Buccal Tablets: Formulation and Assessment : Pharmaceutical sciences- Pharmaceutics - Sequeira, Chrishmitha; P Muchalambe, Sujatha; Abdul Ahad, Hindustan; Jayanna, Abhishek; Syiemlieh, Pynskhemlin; Poojari, Shreya J (International Journal of Life Science and Pharma Research, 2023)
Diabetes is a chronic illness that affects how the body converts food into energy. Numerous organs may be harmed asa result of poor diabetes control. The primary goal of the research project is to prepare and assess mucoadhesive buccal tabletsof nateglinide for type 2 diabetes treatment, employing HPMC K100, Chitosan, and sodium alginate as mucoadhesive polymersalone and in a mixture through direct compression. The assessment parameters include thickness, hardness, weight variation,friability, drug content, swelling index, surface pH, in-vitro drug release, and ex-vivo mucoadhesive strength. FTIR analysis indicatedno drug-excipient interaction. Physical parameters (thickness, hardness, weight variation, friability) adhered to pharmacopoeiastandards, while drug content ranged from 83.65 to 99.76%. The swelling index varied from 100±7.64 to 147.5±2.89%. FormulationF5 (Sodium alginate) exhibited the highest drug discharge (92.1±2.37%), while F8 (HPMC K100 and Sodium alginate) demonstratedsustained discharge (79.1±2.13% at 8 h) and the highest mucoadhesive strength (33.0±2.00 g). Discharge kinetics followed zeroorder (F1, F3, F4, F7, and F9) and Korsemeyer Peppas models (F2, F5, and F6). The study concludes that the potential of theseformulations for controlled drug discharge and oral mucosal adhesion in diabetes management.Keywords: , , , , ,